Hubungan Delayed Cord Clamping terhadap Kenaikan Berat Badan Neonatus - Rachma Anandita, Mella Yuria; Anggraeni, Legina; Nurfaizah, Nurfaizah (Jurnal Kesehatan, 2022)
Delaying clamping and cutting the umbilical cord is one of the efforts that can be done to increase the growth of neonates. The increase in neonate weight at the age of 28 days with a delay in cutting the umbilical cord was 1499.29grams. This study aims to analyze the relationship between delayed cord clamping and weight gain in neonates. The research design was cross-sectional using secondary data in the mother's and baby's medical records. The population of this study was all mothers who gave birth normally from two Independent Midwife Practices in the Jagakarsa area, South Jakarta and the sampling technique used was the purposive sampling technique. Data analysis using Chi-Square Test. The results showed that from 50 respondents, 82.4% of neonates experienced weight gain during delivery with delayed cord clamping. The results of the bivariate analysis obtained a significance value of 0.0001, this indicates that there is a relationship between the Delayed Cord Clamping method and the weight gain of newborns up to the neonatal period. The average weight gain of neonates with Delayed Cord Clamping was 1308.57 grams, while the weight gain of neonates without DCC was 781.25grams. The Delayed Cord Clamping method can increase the growth of neonates because the baby will get more blood containing oxygen, food, and antibodies. Babies get nutrients that affect their growth. It is hoped that every maternity mother who meets the requirements can delay the umbilical cord for 1-3 minutes so that it can increase the baby's hemoglobin level which can help the neonate's weight gain.